THE ROLE OF ACTIVITY RATIO IN MODERATE INFLUENCE OF PROFITABILITY ON COMPANY VALUE (Empirical Study of Companies Listed on the IDX30 Index for the 2018-2023 Period) - Devililis Safitri; Akhmadi; Enis Khaerunnisa (Jurnal Riset Multidisiplin Edukasi, 2025)
Increasing company value is a long-term goal of a company because it will have an impact on prosperity for shareholders. When assessing a company, investors often look at how the company can maximize profits and how well the company's assets are utilized to generate those profits. This research aims to determine the contribution of profitability to company value with the activity ratio as a moderating variable. The population in this study are IDX30 index companies listed on the IDX in 2018-2023. The sampling method used in this research was purposive sampling. Through this method, 14 companies were obtained that could be observed during 2018-2023 (6 years), so the total observation data in this research was 84. The analysis techniques used in this research were classical assumption testing and hypothesis testing (t-test and moderated regression analysis (MRA)) with the help of the SPSS 25 analysis tool. The research results explain that profitability has a positive influence on company value. The activity ratio also positively influences company value and contributes to strengthening the relationship between profitability and company value.